Evidence of a Right Ear Advantage in the absence of auditory targets. Issue 1 (December 2018) - Prete, Giulia; D'Anselmo, Anita; Brancucci, Alfredo; Tommasi, Luca
Abstract The Right Ear Advantage effect (REA) was explored in a white noise speech illusion paradigm: binaural white noise (WN) could be presentedi) in isolation (WN condition), ii) overlapped to a voice pronouncing the vowel /a/ presented in the left ear (LE condition), iii) overlapped to a voice pronouncing the vowel /a/ presented in the right ear (RE condition). Participants were asked to report in which ear the voice has been perceived. The voice could be female or male, and it could be presented at 4 different intensities. Participants carried out the task correctly both in LE and in RE conditions. Importantly, in the WN condition the "right ear" responses were more frequent with respect to both the chance level and the "left ear" responses. A perceptual REA was confirmed both in LE and RE conditions. Moreover, when the voice was presented at low intensities (masked by WN), it was more frequently reported in the right than in the left ear ("illusory" REA). A positive correlation emerged between perceptual and illusory REA. Potential links of the REA effects with auditory hallucinations are discussed.